Cerebral venous sinus thrombosis presenting in pregnancy and puerperium - Dangal, Ganesh (BMJ Publishing Group, 2009)
Cerebral venous sinus thrombosis (CVST) during pregnancy and puerperium is an uncommon diagnosis. CVST can present with wide range of symptoms and signs, and most of the time it is left undiagnosed. Here, three cases of CVST in early pregnancy and puerperium in young women who presented with seizure attacks, altered sensorium and severe headache, respectively, are reported. Subsequent imaging with MRI and magnetic resonance venography (MRV) showed CVST in the first two cases, whereas in the third case it showed a venous infarction. All were treated with low molecular weight heparin followed by warfarin. They all made excellent recoveries and are in regular follow-up.